Strategies of exclusion in non-timber forest product commercialisation in South Africa: an ethnographic study of honeybush (Cyclopia spp.) use and trade - Ndwandwe, Sthembile (Department of Environmental and Geographical Science, 2025)
The Convention on Biological Diversity (CBD) set a precedent for recognising the rights of communities and Indigenous groups in the global commercialisation of biodiversity. South Africa is a signatory to the CBD and has embarked on a programme to commercialise non-timber forest products (NTFPs) by targeting biodiversity-based economies to derive revenue for economic development and socio-economic transformation. Transformation is envisaged to be achieved through job creation and by fast-tracking the participation of historically excluded Black people in biodiversity value chains. Many actors, however, are critical about the ability of NTFP commercialisation to reduce economic marginalisation among poorer members of society; research shows that the integration of NTFPs into regional and global markets often creates dispossession and anti-poor value chains, despite promises of increased equity and benefit sharing. Using the honeybush shrub (Cyclopia spp.) as a lens, a NTFP endemic to South Africa, this thesis aims to contribute to these debates by examining how, if at all, marginalised groups benefit from honeybush commercialisation and the extent to which historical strategies of exclusion configure access to associated value chains. By using varied conceptualisations of exclusion, the study aims to improve understandings of how disadvantage is experienced in the honeybush sector and to suggest approaches that may lead to more transformative biodiversity-based economies. A case study and ethnographic approach were used, with data collection conducted in the Garden Route and Langkloof regions of the Eastern Cape and Western Cape provinces of South Africa. These regions have high densities of the two most commercialised honeybush species, C. intermedia and C. subternata; they also embed long histories of harvesting, tea production and commercialisation by local communities. Building on a layered concept of exclusion and interweaving theories of access, findings show how unresolved colonial enclosures of land, natural resources, epistemologies, and economies in postcolonial and new democracies like South Africa inhibit benefits from NTFPs. The thesis further demonstrates how a reliance on the structural and relational mechanisms of access without secure property rights threatens the ability of marginalised actors to sustain benefits from NTFP commercialisation. A key finding is that efforts to involve marginalised actors can, paradoxically, reinforce structural violence. Addressing this concern requires an understanding of situated histories to enable the implementation of context-specific benefits. Acknowledging that communities living in biodiversity-rich regions are not homogenous is an important component of this approach. The study concludes that socio-economic transformation may need to be preceded by emancipatory transformation. Such an approach would require the state and non-state actors to deliver on structural, systemic, and enabling change by bringing together diverse knowledges, politics, and plural pathways in a transformative manner. The study underscores the importance of land and epistemic justice if biodiversity-based economies are to be equitable.